STUDENTS’ MOOD IN LEARNING WRITING IN ONLINE CLASS PANDEMIC ERA - Sinarman Jaya; Dinda Putri Anggrainy (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The objective of this study was to find out the students’ mood in learning writing in Online Class Pandemic Era at University of Muhammadiyah Bengkulu. This study applied a quantitative research design. A total of 45 sixth semester students Academic Year 2020/2021 participated in this study. The data were collected by using a questionnaire and a guided interview to get information about the students’ emotions in learning writing Online. The writers adapted and modified a new category of emotion categorization, called Hourglass of Emotions, based on the emotions wheel proposed by Cambria et al (2018). The Hourglass Model organizes the primary emotions around four affective dimensions (Pleasantness, Attention, Sensitivity, Aptitude). The finding of this research indicated that the students’ mood in learning writing in Online Class Pandemic Era at University of Muhammadiyah Bengkulu was positive. The students confirmed that they feel positive pleasantness, attention, sensitivity, and aptitude in learning writing by online. It is suggested that both the lecturers and the students to keep the positive mood in process of teaching and learning writing online. For further researchers, this research finding can be used as scientific contribution to investigate the students’ mood in learning writing in Online Class Pandemic Era. Keywords: Students’ Mood, Learning Writing, Online Class, Pandemic Era